Research on the optimization and application of coal pillar width in gob-side entry driving under hard roof condition - Li, Guangyi; Gao, Linsheng; Ma, Qi; Liu, Haoran (Frontiers in Earth Science, 2025)
The width of the coal pillar is a key factor in the success of the gob-side entry driving (GED) technique. This paper, based on the 4,317 working face at Chengzhuang Coal Mine, reveals the stability mechanism of roadway surrounding rock during GED with coal pillars of different widths. Firstly, a main roof failure mechanical model was established using the “internal and external stress field” theory, and the range of the internal stress field was calculated to be 13.6–15.2 m, with the optimal coal pillar width being 10 m. Then, a FLAC3D numerical model was developed and calibrated. Through simulation, the stress and plastic zone evolution characteristics of coal pillars with widths of 5 m, 10 m, 15 m, and 20 m were compared. The results show that a 5 m coal pillar has weak bearing capacity, is prone to plastic failure, and the surrounding rock stability is poor. A 10 m coal pillar exhibits a more uniform stress distribution, smaller plastic zone, and maintains a certain elastic region, with good bearing capacity and no significant stress concentration. It is the optimal design width, offering strong economic and safety advantages. In contrast, 15 m and 20 m coal pillars show significant stress concentration, threatening coal pillar stability and causing resource waste. Finally, a combined control technique of “hydraulic fracturing roof cutting + roof anchor cable + rib anchor cable” with specific parameters was proposed and successfully applied in the 4,317 tailgate. Field monitoring results showed that the surrounding rock deformation stabilized after 55 days, with a maximum deformation of 151 mm, indicating good control effectiveness.